A robust and interpretable gene signature for predicting the lymph node status of primary T1/T2 oral cavity squamous cell carcinoma. Issue 3 (14th October 2021) - Ghantous, Yasmin; Omar, Mohamed; Broner, Esther Channah; Agrawal, Nishant; Pearson, Alexander T.; Rosenberg, Ari J.; Mishra, Vasudha; Singh, Alka; El‐naaj, Imad Abu; Savage, Peter A.; Sidransky, David; Marchionni, Luigi; et al.
Abstract: Oral cavity squamous cell carcinoma (OSCC) affects more than 30 000 individuals in the United States annually, with smoking and alcohol consumption being the main risk factors. Management of early‐stage tumors usually includes surgical resection followed by postoperative radiotherapy in certain cases. The cervical lymph nodes (LNs) are the most common site for local metastasis, and elective neck dissection is usually performed if the primary tumor thickness is greater than 3.5 mm. However, postoperative histological examination often reveals that many patients with early‐stage disease are negative for neck nodal metastasis, posing a pressing need for improved risk stratification to either avoid overtreatment or prevent the disease progression. To this end, we aimed to identify a primary tumor gene signature that can accurately predict cervical LN metastasis in patients with early‐stage OSCC. Using gene expression profiles from 189 samples, we trained K‐top scoring pairs models and identified six gene pairs that can distinguish primary tumors with nodal metastasis from those without metastasis. The signature was further validated on an independent cohort of 35 patients using real‐time polymerase chain reaction (PCR) in which it achieved an area under the receiver operating characteristic (ROC) curve and accuracy of 90% and 91%, respectively. These results indicate that such signature holds promise as a quick and cost effective method for detecting patients at high risk of developing cervical LN metastasis, and may be potentially used to guide the neck treatment regimen in early‐stage OSCC. Abstract : What's new? In oral squamous cell carcinoma (OSCC), early diagnosis of lymph‐node metastasis is essential for successful treatment. However, there is a pressing need for techniques that can improve risk stratification, in order to spare patients without metastases from further invasive surgery. In this study, the authors used a computer model to identify a simple, clinic‐friendly gene panel that can predict which OSCC tumors will likely spread to the lymph nodes. The reliability of this panel underscores the importance of embedding biological knowledge in the training process of cancer predictive models.